SAT0207 Determination of synovial inflammation in the wrist by doppler ultrasonography and mri in patients wtih arthritis. (1st June 2001) - Terslev, L; Savnik, A; Qvistgaard, E; Torp-Pedersen, S; Danneskiold-Samsoe, B; Thomsen, HS; Bliddal, H
Abstract : Background: Synovial membrane volumes obtained by Magnetic Resonance Imaging (MRI) have been suggested as a marker of joint disease activity. 1 Graded power Doppler images has been able to detect treatment response in joint synovium. 2 If ultrasonographic (US) parameters correspond with findings in MRI an alternative method in assessing inflammatory activity would be available. Objectives: To compare the evaluation of signs of synovial activity in patients with arthritis as determined by MRI and DUS respectively. Methods: 11 patients (5 women and 6 men, median age 52, 6 years, range (32–69)) with arthritis were included. All patients were examined by DUS with a 15 MHz linear transducer and by 1.5 T MRI before and after contrast injection. The area and thickness of the synovial membrane were outlined after contrast injection on MRI. US flow pattern of the synovium in the wrist was evaluated by quantitative spectral DUS (n = 10), recording resistance index (RI). The relative RI (rRI) = meanRI/extra synovial RI, was calculated to adjust for changes in peripheral resistance unrelated to the joint. The synovial vascularisation was determined by colour Doppler (n = 10). Using a colour recognition function, all marked pixels were changed to a reference colour and the total amount of pixels finally depicted using a colour histogram. 3 Each patient was evaluated by ESR, CRP and joint assessment. Results: The colour Doppler pixel (CDP) measurements correlated significantly with both max area and thickness of the synovial membrane on post contrast MR images (Rs = 0.88 and 0.84, P < 0.002). Also the rRI values correlated significantly with both max area and thickness of the synovial membrane on post contrast MR images (Rs = 0, 89 and 0, 93, p < 0, 001). Kappa statistics were made on MRI and DUS: Kappa was 0, 8 between the max area and thickness of the synovial membrane on post contrast MR images and the CDP measurements. Kappa was 1, 0 between the max area and thickness of the synovial membrane on post contrast MR images and the rRI values. No correlation was found between ESR, CRP and joint assessment and the imaging modalities. Conclusion: The estimation of synovial inflammatory activity on DUS was comparable with post contrast MRI. DUS appears to be an alternative method to determine inflammatory activity in patients with rheumatic diseases. References: Ostergaard M, et al . Magnetic resonance imaging determined synovial membrane volume as a marker of disease activity and a predictor of progressive joint destruction in the wrists of patients with rheumatoid arthritis. Arthritis Rheum. 1999;42(5):918–29 Newman JS, et al . Power Doppler sonography of synovitis: assessment of therapeutic response preliminary observations. Radiology 1996;198:582–4 Qvistgaard E, et al . Quantitative ultrasonography in rheumatoid arthritis evaluation of inflammation by Doppler technique. Submitted